2021
DOI: 10.32861/jac.81.7.11
|View full text |Cite
|
Sign up to set email alerts
|

Correlations Among Grain Mold Severity, Seed Weight, and Germination Rate of Sorghum Association Panel Lines Inoculated With Alternaria alternata, Fusarium thapsinum, and Curvularia lunata

Abstract: The sorghum association panel was evaluated for grain mold severity, seed weight, and germination rate. The 377 accessions were inoculated with Alternaria alternata alone, a mixture of A. alternata, Fusarium thapsinum, and Curvularia lunata, and untreated water-sprayed control during 2010, 2013-2015 growing seasons at the Texas AgriLife Research Farm, Burleson County, Texas. Each accession was evaluated at least twice. Across accessions, Spearman’s rank correlation was performed for non-parametric correlati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Furthermore, recent studies identified potential linkages between sorghum seed morphology traits and host resistance against fungal pathogens. Significant negative correlations between grain mold severity and seed weight in sorghum were identified in a recent study [39]. Similarly, Ahn et al [29] identified correlations between seed morphology traits (circularity and the distance between IS and CG) and the formation of spots on seedling leaves.…”
Section: Discussionmentioning
confidence: 79%
“…Furthermore, recent studies identified potential linkages between sorghum seed morphology traits and host resistance against fungal pathogens. Significant negative correlations between grain mold severity and seed weight in sorghum were identified in a recent study [39]. Similarly, Ahn et al [29] identified correlations between seed morphology traits (circularity and the distance between IS and CG) and the formation of spots on seedling leaves.…”
Section: Discussionmentioning
confidence: 79%
“…The remaining loci, including a locus on Chr6 and three loci on Chr9) were minor. A highly significant locus on Chr2 (Chr2: 71718582) corresponding to a candidate gene (Sobic.002G353800), which encodes the homeodomain-leucine zipper (HD-Zip) transcription factor family that plays a vital role in plant development and morphogenesis as well as responses to biotic and abiotic stresses ( Prom et al., 2021 ). Interestingly, only a single genomic region on Chr5 (52 Mb) was co-localized between these traits (FW and DW).…”
Section: Resultsmentioning
confidence: 99%
“…Sorghum pathologists have been applying GWAS to identify defense-related genes in sorghum against various fungal diseases, and the studies successfully mined various sources of sorghum resistance in univariate frameworks [ 10 , 11 , 12 , 13 , 15 , 20 , 28 ]. Examples of candidate defense-related genes through univariate GWAS include F-box domain, helix–loop–helix DNA-binding domain, K05280-flavonoid 3’-monooxygenase, leucine-rich repeat, MADS-box protein, MYB transcription factor, oryzalide A biosynthesis, pentatricopeptide repeat, selenium binding protein and xyloglucan endotransglucosylase [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 28 ]. In addition to univariate GWAS, recent studies have extensively applied multivariate GWAS, identifying new sources of SNPs associated with various traits of interest.…”
Section: Discussionmentioning
confidence: 99%
“…Prom et al [ 12 , 17 ] evaluated 377 lines from the Sorghum Association Panel (SAP) for grain mold resistance by inoculating them with either A. alternata alone; a mixture of A. alternata , Fusarium thapsinum and Curvularia lunata ; or untreated water as a control group at the Texas A&M AgriLife Research Farm, Burleson County, Texas. Based on the phenotypic data, a univariate GWAS with over 79,000 SNP loci from a publicly available genotype was conducted by sequencing dataset for the SAP lines [ 18 ] using the TASSEL version 5.2.55 [ 19 ] association mapping software to identify chromosomal locations associated with differences in the grain mold response.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation